Diseño de un plan de mantenimiento en Gaseosas Colombianas S.A.S sede sur, en la línea de producción de agua potable basado en la metodología de mantenimiento centrado en confiabilidad (RCM) (2023)
For the development of the project, the main objective is the design of a maintenance plan at the Gaseosas Colombianas Sur plant (GascolSur) based on the reliability-based maintenance (RCM) methodology within the potable water line and its implementation. First it is essential to understand the technical concepts when designing a maintenance plan. It begins with the collection of data from the entire maintenance area in charge of the line, a period of one year is established, from August 1, 2021 to August 1, 2022 to carry out the analysis. Once you have this data, you start with your organization, since there are variables that will not be taken into account because they did not affect the implementation of RCM.